Optimasi Penggunaan Metode Simulated Annealing Untuk Optimasi Penempatan Posisi Ground Robot - Tri Mutia; Ilham Febrianto; Herminarto Nugroho (JURNAL TEKNOLOGIA, 2020)
VLC (Visible Light Communication) is data communication by sending or receiving signals with light. In this study, the VLC optimization process was carried out for applications that determine the position of the robot on the ground to obtain the desired power. This robot is equipped with a photodiode at the top which serves to measure the strength of the power received. Optimization of the application is done by using the Simulated Annealing (SA) method which is intended to determine the radius of the robot so that the value of the received power equals or approaches the theoretically received power value.